Perceptual and Social Attributes Underlining Age-Related Preferences for Faces - Kiiski, Hanni S. M.; Cullen, Brendan; Clavin, Sarah L.; Newell, Fiona N. (Frontiers in Human Neuroscience, 2016)
Although aesthetic preferences are known to be important in person perception and can play a significant role in everyday social decisions, the effect of the age of the observer on aesthetic preferences for faces of different ages has not yet been fully investigated. In the present study we investigated whether aesthetic preferences change with ageing, with an age-related bias in favouring faces from one’s own age group. In addition, we examined the role of age on both the perceptual qualities and the social attributes of faces that may influence these aesthetic judgements. Both younger and older adult observers provided ratings to images of younger, middle-aged and older unfamiliar faces. As well as attractiveness, the rating dimensions included other perceptual (distinctiveness, familiarity) and social (competence, trustworthiness and dominance) factors. The results suggested a consistent aesthetic preference for youthful faces across all ages of the observers but, surprisingly, no evidence for an age-related bias in attractiveness ratings. Older adults tended to provide higher ratings of attractiveness, competence and trustworthiness to the unfamiliar faces, consistent with the positivity effect previously reported. We also tested whether perceptual factors such as face familiarity or distinctiveness affected aesthetic ratings. Only ratings of familiarity, but not distinctiveness, were positively associated with the attractiveness of the faces. Moreover, ratings of familiarity decreased with increasing age of the face. With regard to the social characteristics of the faces, we found that the age of the face negatively correlated with ratings of trustworthiness provided by all observers, but with the competence ratings of older observers only. Interestingly, older adults provided higher ratings of perceived competence and trustworthiness to younger than older faces. However, our results also suggest that higher attractiveness ratings, together with older aged faces, led to more positive evaluations of competence. The results are discussed within the context of an age-related decline in the differentiation of faces in memory. Our findings have important implications for a better understanding of age-related perceptual factors and cognitive determinants of social interactions with unfamiliar others across the adult lifespan.